Exploring a secondary school educator’s experiences of school violence: a case study - Bester, S (South African journal of education, 2010)
In an increasingly violent society, South African secondary school educators often need to manage violent learners. In the context of a challenging and uniquely South African educational environment, managing this escalating violence often leaves educators battling to cope with increasing demands for learner performance in the midst of an inherited culture of violence and intimidation that spills over into the classroom. We attempt to explore, from an interpretive perspective, the experiences of an educator in a violence-affected educational setting. This includes the educator’s perceptions of the causes, nature and results of violence. The article also unveils the educator's emotional experience and her perceptions of what contributes to the violence.Keywords: bio-ecological systems theory; educator; learners; violence/school violenc